Pedestal analysis of MAST ELMy regimes. (1st April 2022) - Smith, S F; Kirk, A; Chapman-Oplopoiou, B; Clark, J G; Ham, C J; Horvath, L; Maggi, C F; Scannell, R; Saarelma, S
Abstract: Mega Ampere Spherical Tokamak (MAST) pedestal data has been analysed, where a pedestal database of 892 shots was obtained, using the upgraded MAST Thomson scattering (TS) diagnostic. Various edge localised mode (ELM) types are discussed, where characteristics and trends of MAST pedestals are shown. The data from the upgraded TS diagnostic confirms pedestal characteristics found in earlier analysis, using previous TS systems. Using the database, calculations of the bootstrap current are obtained using the different analytical formulae (Sauter and Redl), and comparisons are performed. The upgraded MAST TS system now spans the full plasma mid-plane, such that direct comparisons between inboard and outboard pedestals can be obtained, and asymmetries in the density pedestal width were found. To increase confidence in spherical tokamak pedestal predictions, the assumptions of Europed have been validated from the MAST pedestal data, and a value for the kinetic ballooning mode constraint ( C ∼ 0.145 ) has been obtained. The first spherical tokamak pedestal predictions were performed in Europed and compared to experimental values. Using C  = 0.145 the temperature pedestal height was predicted to within 10% of the experimental value. In addition type II ELMs on MAST are analysed, and stability analysis and parameter scans have been performed using ESSIVE. Similar magneto-hydrodynamic (MHD) stability properties are observed for type I and type II ELMs, originating from the mixed ELM regimes; it is therefore difficult to distinguish these ELMs using the ideal MHD codes.